Manajemen strategi dalam optimalisasi kinerja lembaga keuangan mikro syariah: analisis terhadap implementasi balanced scorecard sebagai alat pengukuran keberlanjutan - Putri, Rosyadah Rensy Dwi Murnisa (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the application of strategic management in optimizing the performance of Islamic microfinance institutions (LKMS) through the implementation of the Balanced Scorecard (BSC) as a sustainability measurement tool. In facing economic dynamics and competition in the financial industry, LKMS are required to have strategies that are not only oriented towards financial profits, but also towards achieving sharia values, customer satisfaction, internal process efficiency, and human resource development. The Balanced Scorecard was chosen because it is able to provide a comprehensive picture of organizational performance from four main perspectives: financial, customer, internal business processes, and learning and growth. This study uses a qualitative descriptive approach with case studies of several LKMS in Indonesia. The results of the analysis indicate that the implementation of the BSC can assist management in formulating integrated and sustainable strategies, increasing operational effectiveness, and strengthening institutional accountability towards Islamic economic principles. In addition, the implementation of the BSC encourages the creation of a balance between worldly and hereafter aspects in the management of Islamic financial institutions. Thus, the Balanced Scorecard becomes a relevant strategic instrument in supporting the sustainability and competitiveness of LKMS in the era of the digital economy and sharia-based inclusive finance.